2017
DOI: 10.5530/pj.2017.2.35
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Antimicrobial Study of Ethanolic Extract of Leaf and Rhizome of Curcuma longa Linn

Abstract: Introduction: Curcuma longa L., botanically related to ginger belongs to the Zingiberaceae family. It is extensively used in Ayurveda, Unani and Siddha medicine as a home remedy for various diseases. Aim: The present study is to compare the antimicrobial activity of the ethanolic extracts from rhizome and leaf of Curcuma longa Linn. Method: In vitro disc diffusion method and serial dilution method has been used to determine the antimicrobial potency against various bacterial pathogens such as Klebsiella pneumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 20 publications
2
19
1
1
Order By: Relevance
“…Some studies have reported mechanisms of action of this plant on fish, such as antimicrobial activity against pathogenic bacteria (Singh et al, 2017), higher stress tolerance during yellowtail lambari transport (Ferreira et al, 2017b) and better growth performance in Nile tilapia (Mahmoud et al, 2017). Therefore, this study aimed to evaluate the effects of dietary supplementation of Curcuma longa hydrolate, with different doses, on hematoimmune parameters and growth performance of Nile tilapia reared in a recirculation aquaculture system (RAS).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported mechanisms of action of this plant on fish, such as antimicrobial activity against pathogenic bacteria (Singh et al, 2017), higher stress tolerance during yellowtail lambari transport (Ferreira et al, 2017b) and better growth performance in Nile tilapia (Mahmoud et al, 2017). Therefore, this study aimed to evaluate the effects of dietary supplementation of Curcuma longa hydrolate, with different doses, on hematoimmune parameters and growth performance of Nile tilapia reared in a recirculation aquaculture system (RAS).…”
Section: Introductionmentioning
confidence: 99%
“…Pengujian daya hambat ekstrak etanol kulit kayu akway dilakukan pada konsentrasi 0- (Singh et al, 2017), daun Andrographis paniculata (Mardiana & Handayani, 2016) dan daun Quercus infectoria (Shariatifar et al, 2014).…”
Section: Hasil Dan Pembahasan Daya Hambat Ekstrak Etanol Pada Beberapunclassified
“…Knowing the phytochemical profile of different parts and different plants is desirable so that one can decide the part to be explored for any particular activity and it can also help one to decide the part(s) to be chosen for any synergistic evaluation. Knowing the phytochemical profile in the beginning of any experiment is desirable than random selection of the plants [31].…”
Section: Page | 626 |mentioning
confidence: 99%